Outpatient Total Extraperitoneal (TEP) for inguinal hernia repair following federal German outpatient operation procedure reform: a preliminary single-center descriptive study of same-day discharge, unplanned admission, and patient-reported outcomes - Julia Michel; Krzysztof Nowakowski; Fabian Nimczewski; Jens Hoeppner; Zsolt Madarasz (BMC Surgery, 2026)
Abstract Background Outpatient hernia repair is becoming increasingly important, particularly with the adoption of minimally invasive techniques such as total extraperitoneal repair (TEP). Following the 2022 reform of the federal German outpatient operation procedure (AOP) catalog, our institution implemented a planned outpatient TEP pathway for selected patients with unilateral inguinal hernia. Methods This preliminary retrospective single-center study included a core cohort of 108 patients who were successfully discharged on the day of surgery after planned outpatient TEP repair between January 2022 and May 2025. A separate analysis included all 153 patients initially scheduled for outpatient TEP repair, of whom 45 required unplanned inpatient admission. Of the 108 patients in the core cohort, 65 (60.2%) completed structured telephone follow-up interviews. Patient-reported outcomes were evaluated exclusively in this subgroup. Results Among all 153 patients initially scheduled for outpatient TEP repair, 108 (70.6%) were successfully discharged on the day of surgery, whereas 45 (29.4%) required unplanned inpatient admission. Among the 108 same-day discharged patients, seven perioperative complications (four intraoperative and three postoperative) were recorded, with no life-threatening bleeding, emergency reoperation, or ICU admission. Patient-reported outcomes were available for 65 of these 108 patients (60.2%). Among respondents, 95.4% stated that they would choose outpatient surgery again, and overall satisfaction was 4.6 ± 0.8 on a 5-point Likert scale (63 valid responses). Conclusion This preliminary single-center experience provides descriptive information on the early implementation of an outpatient TEP pathway under the German AOP framework. Although patients who successfully completed same-day discharge and responded to follow-up reported high satisfaction and perceived safety, the 29.4% unplanned inpatient admission rate, exclusion of admitted patients from the patient-reported outcome analysis, and 60.2% response rate substantially limit conclusions regarding the overall safety, acceptability, and successful implementation of the programme. Prospective multicenter studies with predefined admission criteria and systematic follow-up of all patients are required.